Evaluation of the waste heat utilization from a hot-water-cooled high performance computer via a heat pump. (October 2021) - Feike, Frederik; Oltmanns, Johannes; Dammel, Frank; Stephan, Peter
Abstract: Internet usage, data transfer, and required computing power have seen rapid growth in recent years. Consequently, the number of data centers and their power densities are increasing at an ever-faster rate. Data centers have a huge demand for cooling energy, which is typically dissipated into the environment as waste heat. Due to the mostly urban location of data centers, the usage of their waste heat can play a leading role in decarbonizing urban heat supply. At the Technical University of Darmstadt, a concept for waste heat utilization from the university's own high-performance computer (HPC) was developed. The HPC is cooled with hot water at 40 °C to 45 °C, and the temperature level of the waste heat is further increased via a heat pump before it is fed into the return line of the university's district heating network at 60 °C to 75 °C. The high source temperatures ensure a very efficient operation of the heat pump. This concept was installed on site in 2020 and put into operation at the beginning of 2021. To collect information about the performance of the system, a measurement concept was implemented, which collects data about heat flows and temperatures at various points in the system as well as the electric energy demand of the heat pump. This data is analyzed and measures to optimize the waste heat utilization are derived.